2023
DOI: 10.1093/rb/rbad056
|View full text |Cite
|
Sign up to set email alerts
|

Biaxial stretching of polytetrafluoroethylene in industrial scale to fabricate medical ePTFE membrane with node-fibril microstructure

Abstract: Expanded polytetrafluoroethylene (ePTFE) is promising in biomedical fields such as covered stents and plastic surgery owing to its excellent biocompatibility and mechanical properties. However, ePTFE material prepared by the traditional biaxial stretching process is with thicker middle and thinner sides due to the bowing effect, which poses a major problem in industrial-scale fabrication. To solve this problem, we design an olive-shaped winding roller to provide the middle part of the ePTFE tape with a greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…The interaction between cells and materials is a fundamental issue in the fields of biomaterials and tissue regeneration. Micropillar arrays provide a unique kind of topological surfaces to regulate cell-material interactions. Cell nuclei undergo severe deformation on micropillar arrays with an appropriate dimension, which influenced cell behaviors . Nuclear deformation can also cause chromatin condensation and chromosome relocalization within the nucleus and alter gene expression of the cells. It has been demonstrated that actomyosin and microtubule may synergistically regulate nuclear deformation and chromatin remodeling, finally modulating gene expression .…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between cells and materials is a fundamental issue in the fields of biomaterials and tissue regeneration. Micropillar arrays provide a unique kind of topological surfaces to regulate cell-material interactions. Cell nuclei undergo severe deformation on micropillar arrays with an appropriate dimension, which influenced cell behaviors . Nuclear deformation can also cause chromatin condensation and chromosome relocalization within the nucleus and alter gene expression of the cells. It has been demonstrated that actomyosin and microtubule may synergistically regulate nuclear deformation and chromatin remodeling, finally modulating gene expression .…”
Section: Discussionmentioning
confidence: 99%
“…Raw materials for tissue repair and regenerative medicine have been widely investigated [9], for example, polymers like poly (lactide-co-glycolide) (PLGA) [10][11][12][13], poly (lactic acid) [14,15], gelatin [6,16,17] and polytetrafluoroethylene [18,19], metals like iron [20][21][22], magnesium [23] and titanium [24], and other inorganic materials like calcium phosphate ceramics [25,26] and even carbon nanotubes [27]. The fabricating strategy should adapt to the nature of the raw Figure 1.…”
Section: Introductionmentioning
confidence: 99%